KEHIDUPAN PENGRAJIN CAP TIKUS DI DESA LOBU ATAS KECAMATAN TOULUAAN KABUPATEN MINAHASA TENGGARA - Lungan, Melky (Universitas Sam Ratulangi, 2017)
Cap Tikus is a traditional liquor in Minahasa. He is not a brand. Itscommunal nature caused the Cap Tikus to be hard to protect with theintellectual property law regime. Beverages with 40-50 percent ethanol contentis produced by traditional methods and techniques. The knowledge oftraditional Cap Rat has been done from generation to generation from theirancestors.There is no definite record since when Cap Tikus became a commoditytraded everywhere, but a mild Manuscript of Minahasa cultural history writtenby Jessy Wenas noted that Cap Tikus was already marketed in 1512-1523. It issold by Chinese merchants in the Amsterdam Fort, Manado. Consumers ofSpanish traders and sailors, there is no written document why this drink iscalled Cap Tikus. At that time, this drink is packed in ceramic bottles with amouse tail.In North Sulawesi, initially Cap Tikus was a drink of lasim for thefarmers before going to the garden, which served to warm the body while onthe way, and only circulated North Sulawesi, as the development of the era andthe spread of the people of North Sulawesi Cap Tikus has become a drink thatcan be consumed until To the land of Papua.Craftsman Cap Tikus in North Sulawesi saw a considerable opportunity,especially the craftsmen in the village of Lobu Atas District Touluaan SoutheastMinahasa regency, to be a business in meeting their life needs.Keywords : Cap Tikus, craftsman, Minahasa